A review of the mechanisms of cone degeneration in retinitis pigmentosa. (27th June 2016) - Narayan, Daniel S.; Wood, John P. M.; Chidlow, Glyn; Casson, Robert J.
Abstract: Retinitis pigmentosa (RP) is an inherited condition that features degeneration of rod and cone photoreceptors. In all forms of RP, the genetic mutation is expressed exclusively in rods; however, cones die too. The secondary death of cones in RP remains somewhat mysterious. A better understanding of the mechanisms that cause cone degeneration in RP could lead to novel treatments that preserve cones. There are a number of prevailing theories that attempt to explain cone degeneration in RP. One concept is that cone survival is dependent on trophic factors produced by rods. Another hypothesis is that cones suffer from a nutrient shortage after rods have been lost. Additionally, oxidative stress and pro‐inflammatory microglial activation have also been suggested to play a role in cone death. The present review evaluates the evidence supporting these theories and provides an update on the mechanisms of cone degeneration in RP.